LINGUISTIC EDUCATION PATTERNS IN PUBLIC SERVICE ADVERTISEMENTS OF BANGKALAN TRAFFIC POLICE: A MORPHOSYNTACTIC-CONTEXTUAL STUDY - Wevi Lutfitasari; Maulid Taembo; Sri Rahayu (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2026)
This study examines morphological formations that fill syntactic structures and influence contextual meaning, making them essential in constructing educational messages in public service advertisements (PSAs). It aims to describe these formations and identify their patterns in shaping educational meaning. The study is grounded in a morphosyntactic-contextual framework focusing on educational meaning. This research employs a descriptive qualitative approach, using documentation for data collection and the distributional method for analysis. The data consist of grammatical structures in PSAs published by the Traffic Police Unit (Satlantas) of Bangkalan Resort Police. The findings reveal two main points. First, morphological formations in PSAs are produced through affixation (prefixes, confixes, and suffixes) and function syntactically as Subject (S), Predicate (P), and Adverbial (Adv.), forming the core grammatical structure. These forms represent subject states, actions, targets, and contextual conditions. Second, educational meaning patterns emerge through affixation: (1) forms with me(N)-, di-, ber-, and me(N)-i express motivation, awareness, and positive habits; (2) suffixes -kan and -i convey persuasive or imperative meanings; and (3) ke-an constructions reflect self-awareness. Thus, this study enriches micro-linguistic analysis, enhances insights into morphology and syntax, and provides a basis for linking micro-linguistic analysis with broader contextual elements.